2021
DOI: 10.1093/aobpla/plab006
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific relationships between floral signals and rewards with implications for plant fitness

Abstract: Within-species variation in traits such as petal size or color often provides reliable information to pollinators about the rewards offered to them by flowers. In spite of potential disadvantages of allowing pollinators to discriminate against less-rewarding flowers, examples of informative floral signals are diverse in form and widely distributed across plant taxa, apparently having evolved repeatedly in different lineages. Although hypotheses about the adaptive value of providing reward information have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 175 publications
1
17
0
Order By: Relevance
“…excorticata could function as a signal for greater nectar reward to attract multiple visits by pollinators. Previous studies have shown that pollinators can select for floral traits (Schiestl & Johnson, 2013), and can reliably differentiate among individuals producing different rewards Essenberg, 2021). Similar results were found in this study, as hermaphrodites may benefit from multiple pollinator visits to increase pollen transfer (Bell, 1985), while females are likely to benefit less from repeat visits, especially after fertilisation.…”
Section: -Resultssupporting
confidence: 88%
“…excorticata could function as a signal for greater nectar reward to attract multiple visits by pollinators. Previous studies have shown that pollinators can select for floral traits (Schiestl & Johnson, 2013), and can reliably differentiate among individuals producing different rewards Essenberg, 2021). Similar results were found in this study, as hermaphrodites may benefit from multiple pollinator visits to increase pollen transfer (Bell, 1985), while females are likely to benefit less from repeat visits, especially after fertilisation.…”
Section: -Resultssupporting
confidence: 88%
“…Indeed, most active visitors were wasps, which prefer nectar far more than pollen grains 7 . This phenomenon might represent a type of mimicry between male and female flowers that is typically observed in the genus Begonia 10 (reviewed in 2,11 ). In this case, it can be understood as sexual mimicry in dichogamy.…”
Section: Discussionmentioning
confidence: 89%
“…In general, odour and taste cues of flowers are closely linked from an evolutionary and biochemical perspective in shared chemical pathways (Borghi et al, 2017). Moreover, volatile cues advertising non-volatile floral rewards may allow for an associative learning of FVOCs to corresponding rewards (Dobson and Bergström, 2000, Wright and Schiestl, 2009, Hauri et al, 2021, Essenberg, 2021, provided that the flower is receptive (Knauer et al, 2021, Knauer andSchiestl, 2015). Flower chemicals may also serve other functions such as photoprotection or structural optimisation of the flower (Essenberg, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, volatile cues advertising non-volatile floral rewards may allow for an associative learning of FVOCs to corresponding rewards (Dobson and Bergström, 2000, Wright and Schiestl, 2009, Hauri et al, 2021, Essenberg, 2021, provided that the flower is receptive (Knauer et al, 2021, Knauer andSchiestl, 2015). Flower chemicals may also serve other functions such as photoprotection or structural optimisation of the flower (Essenberg, 2021). FVOC chemodiversity may be related to the chemodiversity of rewards and may also be informative of nutrient content, but this has, to our knowledge, not been explored.…”
Section: Introductionmentioning
confidence: 99%